The Regulation of The Local Government of West Nusa Tenggara Province Regarding Tourism on The Era of Covid 19 - Usman Munir; Baiq Rara Charina Sizi (Magister of Law, Faculty of Law, University of Mataram, 2022)
This study aims to scrutinize the policies issued by Nusa Tenggara Barat provincial government related to the tourism sector during the Covid 19 period and the impact of Covid 19 on the tourism industry in Nusa Tenggara Barat. This study is qualitative research by observing the government policies during the covid period and their impact. The data collection method used in this study were document studies and interviews. Data analysis technique used a qualitative descriptive way, which presented and described all legal materials obtained systematically. This article described some Nusa Tenggara Barat government policies in the form of local legal products during the COVID-19 pandemic era and a number of local government programs to stimulate the tourism sector in Nusa Tenggara Barat, and several policies that can be executed during the covid 19 era. The impact of the COVID-19 pandemic on the tourism industry in Nusa Tenggara Barat decreased the number of tourist arrivals both foreign and domestic, many tourism sector workers were laid off, and hotel income had soared, which resulted in business closures.